Financial Flows from Sacred Basil (Ocimum Sanctum) Based Agroforestry Land-use Systems in Mid Hills of Western Himalayas - Thakurand , N. S. (Indian Forester, 2012)
Investigations on effect of tree-and crop combinations nitrogen levels on economic returns from Ocimum sanctum L. based agroforestry systems were carried out during 2004-2005 and 2005-2006. Three nitrogen doses applied to O. sanctum were 40, 80 and 120 kg/ha. The net returns were calculated on financial (farmer’s land) and economic (rented land) basis. Maximum net financial returns to tune of ` 29136.30 accrued from herbage of O. sanctum grown in association with Peach+Morus+Setaria with application of 120 kg nitrogen/ha, whereas maximum net financial returns (` 35249), from tree and grass component, were obtained from Peach+Setaria. Application of nitrogen progressively increased the herb yield and hence the net returns under all the agroforestry systems. The total net financial returns amounting to 63158 were obtained from Peach+Morus+Setaria+O. sanctum followed by Peach+Setaria+O. sanctum (62945). The maximum benefit:cost ratio (B:C ratio) values to the tune of 3.88 were obtained from Morus+Setaria+O. sanctum system on farmers land (financial), whereas, it was 1.78 from Peach+Setaria+O. sanctum system supposing the enterprise (crop) have been taken on rented land (economic).